2012
DOI: 10.1186/1556-276x-7-663
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and photocatalytic properties of silicon nanowires by metal-assisted chemical etching: effect of H2O2 concentration

Abstract: In the current study, monocrystalline silicon nanowire arrays (SiNWs) were prepared through a metal-assisted chemical etching method of silicon wafers in an etching solution composed of HF and H2O2. Photoelectric properties of the monocrystalline SiNWs are improved greatly with the formation of the nanostructure on the silicon wafers. By controlling the hydrogen peroxide concentration in the etching solution, SiNWs with different morphologies and surface characteristics are obtained. A reasonable mechanism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…Liu et al used SiNWs elaborated by metal-assisted electroless etching in a solution containing HF/H 2 O 2 as photocatalysts for the photodegradation of Rhodamine B. Different concentrations of H 2 O 2 were experimented and they found that a concentration of 20% gives the best photocatalytic activity; a degradation of 35% was obtained after 5 h of irradiation under Xe arc lamp [9]. Qu et al show that unmodified and Pt-modified porous silicon nanowires can be used as effective photocatalysts for the degradation of organic dyes and toxic pollutants under visible irradiation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al used SiNWs elaborated by metal-assisted electroless etching in a solution containing HF/H 2 O 2 as photocatalysts for the photodegradation of Rhodamine B. Different concentrations of H 2 O 2 were experimented and they found that a concentration of 20% gives the best photocatalytic activity; a degradation of 35% was obtained after 5 h of irradiation under Xe arc lamp [9]. Qu et al show that unmodified and Pt-modified porous silicon nanowires can be used as effective photocatalysts for the degradation of organic dyes and toxic pollutants under visible irradiation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the examples given in this chapter, there are many more potential applications like optical devices [142,143], thermoelectric devices [144], catalysts [145] and even more [146]. It is therefore expected that silicon nanowire technology will evolve as a very versatile supplement to the existing silicon technology.…”
Section: Discussionmentioning
confidence: 98%
“…Silicon nanowires (SiNWs), with good surface hydrophilicity, mechanical robustness, and chemical stability could be the potential supporting materials for strengthening the photocatalytic activity of Cu 2 O nanostructures, rendering a promising design of visible-responsive photocatalysts [812]. Moreover, SiNWs further possessed highly visible-absorption capability due to confining the incident lights through the effects of multiple scattering [11].…”
Section: Introductionmentioning
confidence: 99%